Legal Analysis Of Combating Bullying In Children As An Act Of Violence In The Analysis Of Law Number 35 Of 2014 Amending Law Number 23 Of 2002 - Adi Herisasono; M. Suja’i; Didik Prihantoro; Meiko Hendra Setiawan (JURNAL HUKUM SEHASEN, 2023)
The purpose of this research is to analyze the prevention of bullying against children, which can be categorized as a criminal act under Law Number 35 of 2014 amending Law Number 23 of 2002 concerning child protection, as well as to analyze the punishment system used in criminal acts of bullying against children. This study employs a research approach based on primary legal materials by examining theories, concepts, legal principles, and regulations. The research results indicate that forms of bullying against children categorized as criminal acts are found in the Child Protection Law: Article 54 and Article 76C of the Child Protection Law, and in the Criminal Code: Defamation (Article 310 paragraph 1), Deprivation of Liberty (Article 333), Unpleasant Conduct (Article 335), and Assault (Article 351). The punishment system used for bullying perpetrators is divided into various types of punishment. Criminal punishments for children who are perpetrators of bullying take the form of warnings, religious guidance, non-institutional rehabilitation, community service or supervision, vocational training, institutional rehabilitation, and imprisonment.